Conceptualizing a model for the use of software as a service to improve the dynamic capabilities of small and medium enterprises in healthcare sector - P. Makelana; R. Kekwaletswe; M. A. Segooa (International Journal of Science Annals)
Background and Aim of Study: To remain competitive in today’s digital society, Small and Medium Enterprises (SMEs) in the healthcare sector need to consider effective ways to improve their dynamic capabilities (DCs) using Software as a Service (SaaS). SaaS and DCs are current key issues in both academia and practice. The aim of the study: to develop the conceptual model for the use of SaaS to improve the DCs of healthcare SMEs in South Africa. Materials and Methods: The study employed Task-Technology Fit (TTF) and Fit Viability Model (FVM) as a lens to develop a model for the use of SaaS to improve the DCs of healthcare SMEs. To achieve the aim of the study, a deductive approach was followed. The study population was healthcare SMEs, in South Africa. The sampling frame was 384 randomly selected SMEs, in a self-administered survey. Results: The study results show that customer service (β=0.125, p<0.05), sharing information (β=0.132, p<0.05), internet access (β=0.057, p<0.05), data security (β=0.022, p<0.05), top management support (β=0.427, p<0.05), competitive pressure (β=0.178, p<0.05), viability (β=0.325, p<0.05) and task-technology fit (β=0.032, p<0.05) are highly significant on the use of SaaS to improve the DCs of healthcare SMEs. While finance (β=0.235, p>0.05) and infrastructure (β=0.052, p>0.05) were found to be less significant. Conclusions: The conceptual model was developed to identify and explain the factors influencing the use of SaaS to improve the DCs of healthcare enterprises. This model is based on TTF, FVM and external constructs (organisational and environmental characteristics) that are key to improving the DC of South African healthcare SMEs